Perspektif Penegakan Hukum Progresif dalam Judicial Review di Mahkamah Konstitusi - Ja'far Baehaqi (Jurnal Konstitusi, 2016)
The Amendments of the 1945 Constitution after reformation era brings the consequences of the necessity to adjust legislation under the constitution, either by elaborating new legislation or change the existing ones as well as through the elaboration of the rights to constitutional review against that legislation. On the other hand, the Amendment of the 1945 Constitution introduced the Constitutional Court as a court for constitutional matters of which one of the jurisdictions is to review laws against the 1945 Constitution. Since the beginning, as stated in Law No.24 of 2003 on Constitutional Court, the right to constitutional review has been given half-heartedly. To that fact, the Constitutional Court Law contains: restrictions of laws that may be tested, filing requirements, categorization of the verdict, and the composition of the constitutional judges. In the perspective of progressive law, the Constitutional Court’s ignorance of that restrictions considered as contrary to the constitution itself. However, in certain cases, especially related to the filing requirement for constitutionality review, The Constitutional Court is still locked by the restrictions given by Constitutional Court Law, even it is institutionalized through jurisprudence.